Observations of a high-pressure phase creation in oleic acid - Kosciesza, Rafal; Kulisiewicz, Leszek; Delgado, Antonio (High Pressure Research, 2010)
Oleic acid is one of the unsaturated fatty acids which frequently appears in food products such as edible fats and oils. A molecule of oleic acid possesses a double carbon bond, C=C, which is responsible for a transition to a new phase when pressure is applied. This work presents the results of optical observations of such a transition. The observations were made in two cases, the first being static p-T conditions under 60MPa at 20C and the other the dynamic application of the pressure up to 350MPa. The obtained visualization reveals differences in the creation of the phase and in its further appearance. Some crystal forms may be recognized. These results tend to be of interest for food engineers due to increasing interest in high-pressure food preservation among nutritionists and medical scientists concerned with fatty acids.
UnivIS-Import:2015-03-09:Pub.2010.tech.ITC.stmmec.observ
Keywords: Crystallization; High-pressure phase transition; Oleic acid